1992
DOI: 10.1093/oxfordjournals.annonc.a058104
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of quality of life assessment in a randomized phase III trial of small cell lung cancer

Abstract: Between 1985 and 1990 the Swiss Group for Clinical Cancer Research (SAKK) for the first time assessed quality of life (QL) variables in 188 patients in a multicenter small-cell lung cancer trial that compared two different regimens of combination chemotherapy. QL-assessment was scheduled at the beginning of each of the six treatment cycles. The self-rating QL questionnaire included an early version of the EORTC QL questionnaire, a mood adjective checklist (Bf-S) and a single linear analogue scale (LASA) measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 10 publications
1
11
0
2
Order By: Relevance
“…No cases of any grade of radiation induced myelopathy or pneumonitis were detected in any of the patients in both arms during the follow up times. These results are in accordance with some previous randomized trials which reported dysphagia as main toxicity of treatment with no differences among different fractionation schedules used in these trials 9,12 while other trials reported more dysphagia in the short course hypofractionated arm 15 and two trial reported more dysphagia in the more protracted regimen 16 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No cases of any grade of radiation induced myelopathy or pneumonitis were detected in any of the patients in both arms during the follow up times. These results are in accordance with some previous randomized trials which reported dysphagia as main toxicity of treatment with no differences among different fractionation schedules used in these trials 9,12 while other trials reported more dysphagia in the short course hypofractionated arm 15 and two trial reported more dysphagia in the more protracted regimen 16 .…”
Section: Discussionsupporting
confidence: 92%
“…The major concern related to the use of hypo fractionated treatment schedules is their potential inferiority in terms of overall survival as shown in three RCTs 15 . Some evidence exists that higher RT doses result in a modest increase in survival, although at the expense of higher acute toxicity 16 .…”
Section: Discussionmentioning
confidence: 99%
“…(1998) allowed a window of ±2 weeks; measurements within 2 weeks following randomization were regarded as the baseline measurement and measurements during weeks 3–6 were regarded as follow‐up measurements. Hürny et al . (1992) accepted 0–8 days before the beginning of the cycle as correctly scheduled questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Compliance, the number of forms completed at the correct timepoint as a proportion of the number expected, has been reported to range from 23% to 96% in various trials (Hurny et al, 1992). Compliance, the number of forms completed at the correct timepoint as a proportion of the number expected, has been reported to range from 23% to 96% in various trials (Hurny et al, 1992).…”
Section: Missing Datamentioning
confidence: 99%